Melatonin in Infertility - Eryılmaz, Özlem Gün; Sarıkaya, Esma (Gynecology Obstetrics & Reproductive Medicine, 2011)
Melatonin, is the primary synchronizing agent acting primarily on the circadian sleep pattern and has some roles in reproduction. Melatonin receptors have been identified in suprachiasmatic nuclei, pars tuberalis, ovary, uterus, follicular cells, and the oocyte. Melatonin is also a direct free radical scavenger and modulates the oxidative environment in the reproductive tract. It serves as an anti-oxidant agent and protects the oocyte and the embryo from oxidative damage. In this review article, we summarized the likely fertility impairing activity of melatonin in the infertility treatments.